1968
DOI: 10.1128/jb.96.1.184-190.1968
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Composition of Nuclear and Mitochondrial Deoxyribonucleic Acid of Fungi

Abstract: The buoyant density of nuclear and mitochondrial deoxyribonucleic acid (DNA) from 14 species of fungi was determined by CsCl density gradient equilibrium centrifugation. The buoyant density of both types of DNA was the same for all three Mucorales analyzed. The buoyant density of mitochondrial DNA was significantly lower than that of the nuclear DNA for nine species of Ascomycetes and two species of Basidiomycetes. No simple correlation could be obtained from the comparison

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1969
1969
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…author (45,51) are in good agreement with those listed in Table 8. The same can be said for the few others also listed in Table 2.…”
Section: And 5)supporting
confidence: 86%
See 1 more Smart Citation
“…author (45,51) are in good agreement with those listed in Table 8. The same can be said for the few others also listed in Table 2.…”
Section: And 5)supporting
confidence: 86%
“…The procedure used for DNA extraction and purification is a combination of the method of Cheng and Sueoka (14) and of that of Marmur (33). Although it has been described in detail elsewhere (51), one might mention that it involves the use of Pronase and amylase in order, respectively, to decrease the number of protein extractions and to eliminate or reduce contamination of DNA preparation by polysaccharides which, as we will show later, may introduce artifacts in centrifugation profiles. DNA concentration was estimated by optical density measurements at 260 nm (ODw) using the equivalent of 50 Ag of DNA/ml per unit OD,w.…”
Section: Methodsmentioning
confidence: 99%
“…Some features of the zygomycetous fungi make investigation of their mtDNA quite di¤cult. Since the GC contents of the mitochondrial and nuclear DNA do not di¡er signi¢cantly [11], CsCl-bisbenzi-mide isopycnic centrifugation (which has proved useful for most other fungi [12]) is not an applicable method for mtDNA puri¢cation from these organisms. Another approach, mtDNA puri¢cation based on isolation of the mitochondria after freeze-fracturing of the cells, was used previously for characterization of M. racemosus mtDNA [3].…”
Section: Resultsmentioning
confidence: 99%
“…However, on the basis of a detailed study of Mucor subtilissimus DNA, it appears by analogy that buoyant densities equivalent to less than 1.680 g/cm3 (20% GC) might correspond to a "pseudo-satellite" composed of a polysaccharide contaminated with DNA (Moyer and Storck, unpublished data). Also, it was shown in a recent study (13) that fungal mitochondrial DNA had a GC content (calculated from buoyant density measurements) ranging from 28 to 44% for the DNA OF YEASTS 14 species which were analyzed. Since the majority of the satellite bands found in the DNA of the yeast analyzed in the present work had percentage GC within that range, it is suggested that they were of mitochondrial origin.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were ground in liquid N2 and the DNA was extracted and purified as described elsewhere (13). When this procedure failed to yield DNA preparations with a molecular weight suitable for buoyant density analysis, it was replaced by that of Smith and Halvorson (10) except that an incubation with ca-amylase (13) was included and isopropanol precipitation (4) was omitted. The two procedures were tried on some of the yeasts and yielded DNA preparations with identical buoyant density.…”
Section: Methodsmentioning
confidence: 99%